Conference report from the 2012 AHA scientific sessions in Los Angeles. (August 2013) - Westenbrink, B Daan; Edwards, Andrew G; Miyamoto, Shigeki
<x xml:space="preserve">Abstract</x> The 2012 Scientific Sessions of the American Heart Association was held on November 3 – 7 in Los Angels, California. It covered up-to-date research on both basic- and clinical-cardiovascular science. We describe the highlights of the meeting focusing on basic science and clinical cardiology. More specifically we will discuss new insights on arrhythmias, cardiac cell death/survival and clinical studies involving novel and unique treatment paradigms.